Red cell distribution width and carotid atherosclerosis progression The Tromsø Study - Lappegård, Jostein; Ellingsen, Trygve S.; Vik, Anders; Skjelbakken, Tove; Brox, Jan; Mathiesen, Ellisiv B.; Johnsen, Stein Harald; Brækkan, Sigrid K.; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2015)
Red cell distribution width (RDW), a measure of the size variability of circulating erythrocytes, is associated with cardiovascular morbidity and mortality. We aimed to investigate whether RDW was associated with progression of atherosclerotic plaques in subjects recruited from the general population. Baseline characteristics, including RDW, were collected from 4677 participants in the fourth survey of the Tromsø Study conducted in 1994/95. Prevalence of carotid plaques and total plaque area (TPA) were assessed by ultrasonographic imaging at baseline and after seven years of follow-up. Generalised linear models were used to analyse change in TPA across tertiles of RDW. Change in TPA was significantly higher across tertiles of RDW in crude analysis and in multivariable analysis adjusted for cardiovascular risk factors. The mean change in TPA increased from 5.6 mm2 (4.9–6.4) in tertile 1 (RDW ≤ 12.6 %) to 6.7 mm2 (5.9–7.6) in tertile 3 (RDW ≥ 13.3) in multivariable analysis adjusted for body mass index, total cholesterol, HDL cholesterol, systolic blood pressure, self-reported diabetes, smoking status, platelet count, white blood cell count, and hs-CRP levels (p for trend 0.003). A 1 % increase in RDW was associated with 0.6 mm2 (0.1–1.2) increase in TPA in multivariable analysis (p=0.03). RDW was associated with progression of atherosclerosis after adjustments for traditional atherosclerotic risk factors. Our findings suggest that the link between RDW and cardiovascular morbidity and mortality may be explained by atherosclerosis.
Keywords: Atherosclerosis; cardiovascular disease; cohort studies; epidemiology; erythrocyte indices